G184(P) Hospital classrooms: a novel concept in the developing world. (12th March 2018) - Sen, S; Deshpande, A; Gadgil, P; Singhal, T
Abstract : Introduction: Though most tertiary paediatric centres in UK have been running hospital schooling programmes for years, the idea is almost non existent in developing countries. It seems that schooling hospitalised children is either non existent or forgotten, or remains a very low priority for families in the developing world. Even where it does exist, most parents, attending doctors and health care staff seems to be unaware of its benefits. Education is a fundamental right of all children including those in a hospital. Place of study: We are a tertiary paediatric centre, amongst the first in the sub-continent to start a hospital teaching programme with specially appointed teaching staff. Outcome: The initial response to this initiative was not very encouraging with an average daily attendance of 5.6% of admitted children. Overtime it has improved but still remains to less than 16% of admitted children. 92% of children attending the classroom are between 4 to 7 years of age. Children above 10 years were reluctant to attend and surprisingly their parents also supported them. When we tried to ascertain the reasons for the reluctance, 71% stated that their child is resting and needs to recover and 62% stated that they do not want to burden their children with studies during illness. When we looked at awareness about the existing hospital teaching programme, 55% of the attending health care workers including doctors and nurses throughout the hospital were not aware of such an initiative provided by the hospital and 85% of parents were unaware about such facilities provided by the hospital. We are now in the process of remedying this deficiency with parental and staff awareness programmes. Till date hospital classroom initiative has helped us to identify 14 cases of learning difficulties. Conclusion: As paediatricians, we should take responsibility to ensure that all children have access to appropriate education, even while they are hospitalised. For children undergoing treatment, school can offer a familiar and reassuring routine, as well as a feeling of being in step with their peers in the outside world. This concept needs to be popularised further specially in the developing world.